Open justice - Mohamed Ramli, MNI (2018)
This thesis seeks to explain the nature of the open justice principle and elaborates its justification. This thesis argues that the open justice principle's underlying idea is in the concept of “inclusivity” in that members of the public are recognised as “participants” in court adjudication alongside the litigants who are privy to a case before the court. It moves away from the conventional wisdom where court adjudication is framed purely based on the tripartite arrangement of judges and two opposing litigants (plaintiff and defendant; the prosecutor and the accused person). It also challenges the orthodoxy that regards members of the public as bystanders and observers, sitting at the periphery of the judicial process with negligible role and interest. Members of the public are given a space and assumed to be part of the court adjudication by making the adjudicatory process open, accessible and transparent. In this context, publicity is treated as the medium whereby members of the public are brought into the trial process. While acknowledging that open justice may be justified on many grounds, this research concludes that the primary factor that explains the applicability of the open justice principle in the judicial process and the recognition of members of the public as “participants” in court adjudication is because court adjudication is a process of public enforcement or application of legal norms by the judicial authority. It becomes the primary justification as (i) it encapsulates the basis of bringing in members of the public into the adjudicatory process; (ii) it integrates other plausible justifications which may additionally explain the need for transparency in court adjudication; (iii) it explains the inapplicability of the open justice principle in the non-judicial dispute settlement process; and (iv) it is relevant and applicable to all types of cases in both civil and criminal trials.